Do differences in diagnostic criteria for late fetal growth restriction matter - Mylrea-Foley, Bronacha; Napolitano, Raffaele; Gordijn, Sanne; Wolf, Hans; Lees, Christoph C; Stampalija, Tamara (American journal of obstetrics & gynecology MFM, 2023)
BACKGROUND: Criteria for diagnosis of fetal growth restriction differ widely according to national and international guidelines, and further heterogeneity arises from the use of different biometric and Doppler reference charts, making the diagnosis of fetal growth restriction highly variable. OBJECTIVE: This study aimed to compare fetal growth restriction definitions between Delphi consensus and Society for Maternal-Fetal Medicine definitions, using different standards/charts for fetal biometry and different reference ranges for Doppler velocimetry parameters. STUDY DESIGN: From the TRUFFLE 2 feasibility study (856 women with singleton pregnancy at 32+0 to 36+6 weeks of gestation and at risk of fetal growth restriction), we selected 564 women with available mid-pregnancy biometry. For the comparison, we used standards/charts for estimated fetal weight and abdominal circumference from Hadlock, INTERGROWTH-21st, and GROW and Chitty. Percentiles for umbilical artery pulsatility index and its ratios with middle cerebral artery pulsatility index were calculated using Arduini and Ebbing reference charts. Sensitivity and specificity for low birthweight and adverse perinatal outcome were evaluated. RESULTS: Different combinations of definitions and reference charts identified substantially different proportions of fetuses within our population as having fetal growth restriction, varying from 38% (with Delphi consensus definition, INTERGROWTH-21st biometric standards, and Arduini Doppler reference ranges) to 93% (with Society for Maternal-Fetal Medicine definition and Hadlock biometric standards). None of the different combinations tested appeared effective, with relative risk for birthweight <10th percentile between 1.4 and 2.1. Birthweight <10th percentile was observed most frequently when selection was made with the GROW/Chitty charts, slightly less with the Hadlock standard, and least frequently with the INTERGROWTH-21st standard. Using the Ebbing Doppler reference ranges resulted in a far higher proportion identified as having fetal growth restriction compared with the Arduini Doppler reference ranges, whereas Delphi consensus definition with Ebbing Doppler reference ranges produced similar results to those of the Society for Maternal-Fetal Medicine definition. Application of Delphi consensus definition with Arduini Doppler reference ranges was significantly associated with adverse perinatal outcome, with any biometric standards/charts. The Society for Maternal-Fetal Medicine definition could not accurately detect adverse perinatal outcome irrespective of estimated fetal weight standard/chart used. CONCLUSION: Different combinations of fetal growth restriction definitions, biometry standards/charts, and Doppler reference ranges identify different proportions of fetuses with fetal growth restriction. The difference in adverse perinatal outcome may be modest, but can have a significant impact in terms of rate of intervention.
Keywords: Birth Weight; ultrasonografie dopplerovská; Pregnancy; těhotenství; Fetal Weight; lidé; Female; Fetal Growth Retardation; ženské pohlaví; Ultrasonography, Doppler; Humans; růstová retardace plodu; porodní hmotnost; hmotnost plodu